Siegfried Kracauer's American writings : essays on film and popular culture - Kracauer, Siegfried, 1889-1966 (Weimar and now: German cultural criticism, 2012)
Siegfried Kracauer (1889-1966), friend and colleague of Walter Benjamin and Theodor Adorno, was one of the most influential film critics of the mid-twentieth century. In this book, Johannes von Moltke and Kristy Rawson have, for the first time assembled essays in cultural criticism, film, literature, and media theory that Kracauer wrote during the quarter century he spent in America after fleeing Nazi-occupied Europe. In the decades following his arrival in the United States, Kracauer commented on developments in American and European cinema, wrote on film noir and neorealism, examined unsettl.